Energy systems for an artiﬁcial cross-country skiing tunnel- With focus on snow quality and system boundaries - Fredheim, Sofie (My University, 2019)
The system of an indoor skiing tunnel was ﬁrst deﬁned with a ﬁgure and than simpliﬁed in to three points; cooling, gains and losses for the surrounding air and lastly the amount of snow added to the system. Then the snow quality that was deﬁned the best snow quality was snow at around 0.4 g/dm3. three study visits where done to get a better under standing of the operating and running of tree diﬀerent tunnels in Gothenburg, Torsby and Gällö. From the study visits it was found that the tunnels were barely ventilated and that air leakage was the biggest contributer to the heating of the tunnels. Then the seasonal climate was deﬁned. And the duration of hours that the diﬀerent conditions lasted every year in the mollierchart. FromthisItwasfoundthatthattheheatlossduetoanairleakageof 1 m/s2 the heat gain to the system is approximately 24000 kWh/year. With this it was found that the energy needed to replace the snow in the diﬀerent skiing tunnel was in the range between 120-145 MW. The conclusion drawn form this is that the this area need more research on the are of snow quality in indoor skiing tunnel and with conditions will make the snow to last longer. The skiing tunnels are a perfect place because of its controlled conditions to do this.
Keywords: Indoor skiing tunnel; snow quality; air conditions in Mollier